Pengembangan Media Pembelajaran Berbasis Android untuk Siswa Kelas X Pada Mata Pelajaran Sistem Operasi - Muhammad Khalid Hakky; Rasyid Hardi Wirasasmita; Muhammad Zamroni Uska (Jurnal Pendidikan Informatika (EDUMATIC), 2018)
The purpose of this research are (1) to know the process of developing system learning media (2) to test the feasibility of learning media developed for class X students (3) to find out the students' response to the operating system learning media. This research is a research or development research (R D) adapted from the ADDIE development model. The stages are 5: 1) Analysis, 2) Design, 3) Development 4) Implementation and 5) Evaluation. Data writing techniques in the form of questionnaire research. Validation is carried out by material experts and media experts. The developed media was tested on 20 students. The results showed the level of feasibility of the learning media of android-based operating systems as learning media based on: 1) Expert acquisition material total score of 110.00 in the category "Very Good" and if percentage was scored 85%, category "Very Worthy", 2) Media experts obtained a total score of 97.00 in the "Very Good" category and if percentage was scored 84.35%, "Very Decent" category, Students' response to this media at the time of testing was distributed on average Shows a positive response to the percentage 70%. Thus the Android-based Operating System learning media is used as a learning medium for students of class X majoring in Multimedia material Operating Systems.